Status of Hospital Programs for the Optimization of Antimicrobial Use: Results of the 2022 national survey in Peru. - Mantilla Ponte, Hilda (2022)
Background: The Antimicrobial Optimization Programs (PROA) in Health Institutions are a strategy implemented in various countries. The study: Our objective was to carry out an electronic survey in health establishments that have hospitalization services in Peru. Findings: One hundred seventy establishments (38.4%) responded to the survey between MINSA (90%), ESSALUD (4.2%), Armed Forces - PNP (2.9%) and Private (2.9%). Only 49 (28.8%) had PROA working within their institution. 83.7% had a Director Resolution that they supported in functions and 38.8% reported having a PROA activity plan. The most frequent problems identified are the lack of trained human resources (24.6%), the lack of training and technical assistance (13.1%) and the failure to prescribe antibiotics (11.5%). Conclusion: It is a priority to continue strengthening the PROA in hospitals in the short term with activities that stimulate the rational use of antimicrobials.